Unexpected organellar locations of ESCRT machinery in Giardia intestinalis and complex evolutionary dynamics spanning the transition to parasitism in the lineage Fornicata - Pipaliya, Shweta V; Santos, Rui; Salas-Leiva, Dayana; Balmer, Erina A; Wirdnam, Corina D; Roger, Andrew J; Hehl, Adrian B; Faso, Carmen; Dacks, Joel B (BMC biology, 2021)
BACKGROUND: Comparing a parasitic lineage to its free-living relatives is a powerful way to understand how that evolutionary transition to parasitism occurred. Giardia intestinalis (Fornicata) is a leading cause of gastrointestinal disease world-wide and is famous for its unusual complement of cellular compartments, such as having peripheral vacuoles instead of typical endosomal compartments. Endocytosis plays an important role in Giardia's pathogenesis. Endosomal sorting complexes required for transport (ESCRT) are membrane-deforming proteins associated with the late endosome/multivesicular body (MVB). MVBs are ill-defined in G. intestinalis, and roles for identified ESCRT-related proteins are not fully understood in the context of its unique endocytic system. Furthermore, components thought to be required for full ESCRT functionality have not yet been documented in this species. RESULTS: We used genomic and transcriptomic data from several Fornicata species to clarify the evolutionary genome streamlining observed in Giardia, as well as to detect any divergent orthologs of the Fornicata ESCRT subunits. We observed differences in the ESCRT machinery complement between Giardia strains. Microscopy-based investigations of key components of ESCRT machinery such as GiVPS36 and GiVPS25 link them to peripheral vacuoles, highlighting these organelles as simplified MVB equivalents. Unexpectedly, we show ESCRT components associated with the endoplasmic reticulum and, for the first time, mitosomes. Finally, we identified the rare ESCRT component CHMP7 in several fornicate representatives, including Giardia and show that contrary to current understanding, CHMP7 evolved from a gene fusion of VPS25 and SNF7 domains, prior to the last eukaryotic common ancestor, over 1.5 billion years ago. CONCLUSIONS: Our findings show that ESCRT machinery in G. intestinalis is far more varied and complete than previously thought, associates to multiple cellular locations, and presents changes in ESCRT complement which pre-date adoption of a parasitic lifestyle.
Keywords: endozomální třídící komplexy pro transport; transport proteinů; Biological Evolution; Evolutionary Cell Biology; Excavata; ESCRT; Endosomes; PV; biologická evoluce; Endomembrane; Giardia; Endosomal Sorting Complexes Required for Transport; Parasitism; Giardia lamblia; Protein Transport; endozomy